Numerical solution and errors analysis of iterative method for a nonlinear plate bending problem - Akakpo Amoussou Wilfried; Houédanou Koffi Wilfrid (Results in Applied Mathematics)
This paper uses the HCT finite element method and mesh adaptation technology to solve the nonlinear plate bending problem and conducts error analysis on the iterative method, including a priori and a posteriori error estimates. Our investigation exploits Hermite finite elements such as BELL and HSIEH-CLOUGH-TOCHER (HCT) triangles for conforming finite element discretization. We use an iterative resolution algorithm to linearize the associated discrete problem and study the convergence of this algorithm towards the solution of the approximate problem. An optimal a priori error estimation has been established. We construct a posteriori error indicators by distinguishing between discretization and linearization errors and prove their reliability and optimality. A numerical test is carried out and the results obtained confirm those established theoretically.